Finite Element Simulation Analysis for Dynamic Meshing Force of Straight Tooth Face Gear - Cao Maopeng; Tang Jinyuan; Lei Duncai (Jixie chuandong)
Analysis of the dynamic meshing force of face gear is the important content in the design of face gear drive with high quality.Based on the secondary development of CATIA and the principle of gear machining,the 3Dgeometric modeling of face gear for finite element analysis is obtained.Based on basic theory of contact dynamics,the reasonable finite element analysis model is built and the reasonable parameters are determined.The finite element simulation analysis and study of the dynamic meshing of face gear are carried out by using the ABAQUS,the variation law of the tooth surface contact force and the tooth root bending stress of face gear in the process of continuous mesh and the association law of the among the speed,load and tooth surface dynamic meshing are obtained.It will be provide some reference value for dynamic performance analysis of high-performance face gear drive.